Randomised controlled trial: nutritional supplements to relieve irritable bowel syndrome symptoms by targeting the gut microbiota - Maartje van den Belt; Zhuang Liu; Lonneke Janssen Duijghuijsen; Erwin G. Zoetendal; Ben Witteman; Nicole M. de Roos; Paul Vos; Hauke Smidt; Nicole J.W. de Wit (Journal of Nutritional Science, 2025)
In individuals with irritable bowel syndrome (IBS), eliminating dietary triggers can alleviate symptoms but may lead to nutrient deficiencies and overall health decline. Although various nutritional supplements show promising results in relieving IBS symptoms due to their potential to alter the microbiome, conclusive scientific evidence remains lacking. This exploratory study aims to assess the bifidogenic properties of four nutritional supplement interventions and their impact on IBS-symptoms, faecal microbiota composition, faecal short-chain fatty acid (SCFA) concentrations, stool pattern, and quality of life (QoL), compared to a placebo control. Seventy subjects with IBS, meeting the ROME IV criteria, participated in this randomised, double-blind, placebo-controlled parallel intervention study. Subjects were assigned to one of the four treatment groups, receiving either resistant starch, pea fibre, chondroitin sulfate, protein hydrolysate, or placebo daily for four weeks. Daily reports on stool pattern and gastrointestinal complaints were collected. Stool samples and questionnaires on dietary intake, symptom severity, QoL, and anxiety and depression were collected at baseline and after the 4-week intervention. The results show no significant increase in Bifidobacterium abundance or faecal SCFA levels after the 4-week intervention with any of the four nutritional supplement interventions. While some improvements in symptom severity and QoL were observed within-groups, these were not significantly different from changes observed with placebo. In conclusion, the tested nutritional supplements did not increase Bifidobacterium abundance in subjects with IBS within four weeks. Furthermore, we conclude that future studies should consider a run-in period and a larger sample size to study improvements in IBS symptoms.